2016
DOI: 10.4314/ahs.v16i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients undergoing chemotherapy - a qualitative study of adults attending Uganda Cancer Institute

Abstract: Background: Cancer is a global public health challenge and how patients in countries with poor healthcare infrastructure experience cancer treatment is largely unknown. Purpose: The objective of this study was to describe adult Ugandan cancer patients' experiences of undergoing chemotherapy treatment. Methodology: Using a qualitative descriptive design, seven in-patients with varying cancer diagnoses at the Uganda Cancer Institute were interviewed about their experiences of undergoing chemotherapy treatment; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…To minimize the side effects and improve the psychological well-being of patients, participants in this current study were taken through series of preparation during the initial phase such as dietary requirements which included eating of fruits and vegetables and the importance of avoidance of crowd to prevent opportunistic infections to help them cope and adjust with the effects of treatment. This finding agreed with findings by Suwankhong and Liamputtong (2018): Lai et al (2017) and Wampaalu et al (2016) which indicated breast cancer patients should necessarily employ medically recommended coping and self-adjustment strategies including diet adjustments such as eating lots of fruits and vegetables, exercise and taking enough rest, and engaging in indoor activities to minimize the side effects of chemotherapy. The study further revealed that others isolated themselves as much as possible since they felt their immune system was compromised and they could contract opportunistic infections.…”
Section: Discussionsupporting
confidence: 90%
“…To minimize the side effects and improve the psychological well-being of patients, participants in this current study were taken through series of preparation during the initial phase such as dietary requirements which included eating of fruits and vegetables and the importance of avoidance of crowd to prevent opportunistic infections to help them cope and adjust with the effects of treatment. This finding agreed with findings by Suwankhong and Liamputtong (2018): Lai et al (2017) and Wampaalu et al (2016) which indicated breast cancer patients should necessarily employ medically recommended coping and self-adjustment strategies including diet adjustments such as eating lots of fruits and vegetables, exercise and taking enough rest, and engaging in indoor activities to minimize the side effects of chemotherapy. The study further revealed that others isolated themselves as much as possible since they felt their immune system was compromised and they could contract opportunistic infections.…”
Section: Discussionsupporting
confidence: 90%
“…Cancer is the second most morbidity causing disease, and its treatment procedure is still a therapeutic and economic challenge. Even though, conventional cancer chemotherapy has improved survival rate, they also have grievous limitations [ 1 ]. For instance, chemotherapy has drug distributing nonspecifically all over human body, thus affecting both cancerous and healthy cells.…”
Section: Introductionmentioning
confidence: 99%
“…Receiving chemotherapy treatment was not easy, and the side effects experienced had a negative impact on their bodies and moods. Dealing actively with discomfort and accepting negative impacts in hope of a cure helped to manage the acute complications of their chemotherapy 7 . Cancer patients undergoing chemotherapy experience a variety of symptoms.…”
Section: Resultsmentioning
confidence: 99%